PROCESS-FLOW APPROACH TO DISCLOSURE OF BANKING SYSTEM FINANCIAL STABILITY - Кузнєцова, Анжела; Погореленко, Наталія (Socio-economic relations in the digital society, 2019)
Based on the generalization of the main provisions of stream and process approaches to the management of economic systems, as well as taking into account the links between the basic economic categories, the operation of which discloses the content of approaches, the possibility of their integrated combination as a theoretical basis for deepening the understanding of the stability of the banking system is determined. In order to specify the terminology within the process-flow approach according to the criteria of content load and morphological construction, the study of the essence of monetary and fi nancial fl ows was made and concluded that their interconnection is as follows: financial flows that arise in the process of banking activity, are «accompanied» by the corresponding cash flows. The content of the process-flow approach to study the stability of the banking system is revealed through relationship banking activities and financial flows in the context of the implementation of the transformation functions of banks. In accordance with the process-stream approach, the stability of the banking system is determined on the basis of changes in the parameters of input and output financial flows that represent the movement of fi nancial resources in time in the process of formation, distribution and use. As a result of systematization of the principles of process and fl ow approaches, their synthesis and transformation, in relation to the needs of understanding the stability of the banking system, a list of principles of the process and flow approach is formed. In accordance with certain principles (minimizing risks, dynamism, adaptability, causality, structuring, balancing, targeting achievement and ensuring effi ciency), to ensure the stability of the banking system, it is necessary to: balance the incoming and outgoing fi nancial fl ows of banks; in order to minimize the ongoing monitoring of their fi nancial risks; Continuous tracking of activity parameters, incoming and outgoing financial flows of banks; detection of destabilizing factors of infl uence on their deviation and timely correction of managerial decisions in response to negative changes; taking into account causal links between fi nancial and economic events and balancing of fi nancial fl ows of banks.